THE EFFECT OF PHYSICAL WORK ENVIRONMENT AND NON-PHYSICAL WORK ENVIRONMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) OF EMPLOYEES IN THE PACKING DEPARTMENT OF UMKM XYZ IN CIMAHI CITY - Icha Putri Gunawan; Khaerul Abdurahman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the Micro, Small, and Medium Enterprises (MSMEs) environment, the key to operational success is not only influenced by employee contributions based on their formal duties, but also voluntary behavior. Voluntary employee behavior in helping coworkers without being part of the assigned tasks and not receiving direct rewards is called Organizational Citizenship Behavior (OCB) (Lestari & Octavianty, 2024). The purpose of this study is to determine the influence of the physical work environment and non-physical work environment on Organizational Citizenship Behavior (OCB) both partially and simultaneously. The method used is a quantitative approach with data collection techniques through distributing questionnaires and analyzed using multiple regression which has previously been tested through classical assumptions with the help of SPSS version 27.0. The respondents used in this study consisted of 32 employees in the packing department of MSMEs XYZ, Cimahi City. The results of the study show that partially, the physical work environment and non-physical work environment have a positive influence on Organizational Citizenship Behavior (OCB). Simultaneously, both variables influence Organizational Citizenship Behavior (OCB). This indicates that the more appropriate the physical work environment is in supporting work activities, and the better the non-physical work environment, such as harmony at work, will impact the strength of the Organizational Citizenship Behavior (OCB) demonstrated.